2018
DOI: 10.1002/oby.22140
|View full text |Cite
|
Sign up to set email alerts
|

The Obesity Paradox: A Misleading Term That Should Be Abandoned

Abstract: The term "obesity paradox" is a figure of speech, not a scientific term. The term has no precise definition and has been used to describe numerous observations that have little in common other than the finding of an association of obesity with a favorable outcome. The terminology has led to misunderstandings among researchers and the public alike. It's time for authors and editors to abandon the use of this term. Simply labeling counterintuitive findings as the "obesity paradox" adds no value. Unexpected findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 21 publications
1
28
0
4
Order By: Relevance
“…11 The International Agency for Cancer Research reviewed ≥1000 observational studies and concluded that there is convincing evidence that a high BMI is associated with an increased risk of developing 13 types of cancer. 15 There are several proposed explanations for the observation that higher BMI is associated with improved overall Figure 1 The effects of body mass index across the cancer continuum. cancer-specific survival or overall survival) is less consistent, and for many malignancies, overweight or obesity is associated with a survival advantage ( Figure 1).…”
Section: Body Mass Indexmentioning
confidence: 99%
“…11 The International Agency for Cancer Research reviewed ≥1000 observational studies and concluded that there is convincing evidence that a high BMI is associated with an increased risk of developing 13 types of cancer. 15 There are several proposed explanations for the observation that higher BMI is associated with improved overall Figure 1 The effects of body mass index across the cancer continuum. cancer-specific survival or overall survival) is less consistent, and for many malignancies, overweight or obesity is associated with a survival advantage ( Figure 1).…”
Section: Body Mass Indexmentioning
confidence: 99%
“…There is no precise definition to the term, and numerous and sometimes loosely related observations have been summarized under this seemingly paradoxical finding. 35 The core observation, however, of an inverse association of body weight with outcome in patients with prevalent diseases has been confirmed in multiple reports and in numerous patient cohorts, in different ethnic groups, 37 over a wide spectrum of cardiovascular diseases and disease severity and using various methods. With an increasing bulk of data confirming a survival benefit related to overweight and mild obesity in such diseases, and based on pathophysiologic concepts to explain these findings, there is sufficient scientific evidence to abandon the term 'paradox'.…”
Section: Applying Emerging Data In Clinical Decision-making-evolving mentioning
confidence: 94%
“…The extra weight (if ‘extra’ is even a proper term here) may protect these patients against ravages of diseases such as heart failure, advanced chronic kidney disease, terminal cancers, as well as sarcopenia of old age . Arguments that this is just an artefact of selection bias are undermined by the observation that the same phenomenon is seen even for chronic diseases that are not obesity‐related …”
Section: Unjustified Generalization Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations